Penentuan Koefisien Redaman Zat Cair (Air, Minyak Goreng dan Oli) Menggunakan Analisis Osilasi Teredam - Silahooy, Stevi; Latununuwe, Altje; Huliselan, Estevanus K.; Kesaulya, Noke; Nggolaon, Delpina (Pattimura University, 2024)
This research aims to analyze the effect of load mass on the damping coefficient of liquid substances such as water, cooking oil, and oil. The load masses used are 71 grams, 81 grams, 91 grams, and 101 grams. This study employs an experimental method with a damped oscillation analysis approach aided by Origin software. The research results indicate a significant influence of load mass on the frequency (Hz) and damping coefficient (γ) values of the liquid substance, where the larger the load mass, the higher the frequency (Hz) and damping coefficient (γ) values of the liquid substance. The study also examines the damping constants of each liquid substance. The results show that the damping constants of each liquid substance, namely water, cooking oil, and oil, are respectively 0.049 kg/s, 0.107 kg/s, and 0.201 kg/s.